Influence of Tempering Heat Treatment on Mechanical Properties of Welded Mild Steel - Sujakhu, Surendra; Chaudhary, Balkrishna; Panthee, Sabal; Dahal, Dadiram (Kathmandu University Journal of Science, Engineering and Technology, 2023)
An experimental study is performed in this research to investigate the changes in mechanical properties of mild steel during the welding and tempering heat treatment cycle. Four experimental cases were considered; i) as-received, ii) heat-treated, iii) welded, and iv) post-weld heat treated. Both the heat-treated and post-weld heat-treated cases followed the identical tempering process. Charpy and tensile tests were done to investigate the tested specimens’ impact energy and fracture strength. A total of 16 tensile tests and 16 Charpy tests were conducted. Fracture surface studies were performed to determine the types of fracture on samples of all four cases. The results of the Charpy test according to the toughness of samples were: heat-treated > as-received > post-weld heat-treated > welded. Similarly, the tensile test results according to tensile strength were: heat-treated > as-received > post-weld heat-treated > welded. The hardness of samples was predicted from tensile strength, using the correlation of hardness and tensile strength of mild steel. The predicted hardness at four cases of samples was: heat-treated > as received > post-weld heat-treated > welded. It was observed that the strength of welded samples is less as compared to the as-received case and there was an increase in the strength of samples after being heat-treated and post-weld heat treated.